(untitled) (Italian Journal of Public Health, 2009)
Vaccination strategies are recognised as one of the most powerful interventions in the field of Public health worldwide, capable of reducing both morbidity and mortality. There is wide availability of new vaccines, at least in Developed Countries, that have the potential to control infectious diseases, while on the other hand there are new vaccines that will become available in the next few years. This paper aims to describe the different perspectives one could take into account in valuing particularly new vaccines. The epidemiological approach has been one of underlying principles in setting priorities for immunization programs. The introduction in the health market of a new vaccine is based on the assessment of the related burden of infection/disease and the consequent impact on population health. In the economic evaluation approach several types of analysis are available. The budget impact analysis is concerned more with the immediate impact; in this sense cost is considered instead of value as well as giving higher consideration to short-term effects, while cost-effectiveness or cost-utility analysis can be utilised to examine effects in the long term. In the field of vaccinations a public approach through the use of media campaigns or non-profit organisations, might or might not push politicians and physicians to take action to address a perceived health problem via a vaccine. A Health Technology Assessment approach has been developed in some European countries to examine, in a multidisciplinary way, the clinical, economic, organizational, ethical, juridical, social and cultural implications of the introduction or the implementation of a specific technology. The HTA approach in Italy was demonstrated to be a comprehensive tool in assessing the introduction of a new vaccine, giving insight to the issue to several stakeholders, i.e. decision makers, researchers, and patients.